Bichromophoric naphthalene derivatives of diethylenetriaminepentaacetate (DTPA): fluorescent response to H+, Ca2+, Zn2+, and Cd2+. Issue 5 (4th May 2019) - Vera, Moises; Santacruz Ortega, Hisila; Inoue, Motomichi; Machi, Lorena
ABSTRACT: As an effort to design selective fluorescent sensors toward Ca 2+, Zn 2+  and Cd 2+, synthetic and fluorometric studies were performed on four bichromophores, each of which consists of two naphthyl or methynaphthyl units (1- and 2-isomers) linked with a diethylenetriaminepentaacetate (DTPA) chain.  Every bichromophore exhibits naphthalene-monomer emission at 370 nm and excimer emission at 405 nm.  Emission intensities show sensitive pH dependence, from which protonation constants were determined.  Fluorometric titrations with the metal ions were performed at the physiological pH and the conditional formation constants were determined. Naphthyl rings define the stoichiometry and stability of the complexes. The insertion of CH2  spacer intensifies the emission and enhances the selective response to metal ions: the excimer emission is strengthened by 70−100 % with Cd 2+  coordination, weakened by 60 % with Zn 2+, and insensitive to Ca 2+ . The high response of methylnaphthyl bichromophores to Cd 2+  is advantageous in fluorometric analyses. GRAPHICAL ABSTRACT: